Impact of real-time three-dimensional transesophageal echocardiography on procedural success for mitral valve repair - Mori, Mika; Yoshimuta, Tsuyoshi; Ohira, Miho; Yagi, Mariko; Sakata, Kenji; Konno, Tetsuo; Kawashiri, Masa-aki; Tomita, Shigeyuki; Watanabe, Go; Iino, Kenji; Takemura, Hirofumi; Yamagishi, Masakazu; et al. (Journal of echocardiography, 2015)
Background For mitral valve repair, minimally invasive cardiac surgery as well as transcatheter valvular intervention have been developed. Under these conditions, three-dimensional transesophageal echocardiography (3D-TEE) plays a key role for planning the surgical treatment strategy. However, few data exist regarding the role of 3D-TEE in mitral valve repair. Therefore, we examined the impact of 3D-TEE on procedural success of mitral valve repair. Methods and results We examined 86 consecutive patients who underwent mitral valve repair for degenerative mitral valve prolapse. Among them, 39 patients were examined by only two-dimensional transesophageal echocardiography (2D-TEE) and 47 patients underwent 3D-TEE in addition to 2D-TEE. The cardiac surgeons and physicians discussed the repair procedure preoperatively with the echocardiographic images. As a result, 18 patients of the 2D-TEE group and 37 patients of the 3D-TEE group underwent mitral valve repair by small thoracotomy including robotic approach. Simple repair was done in 21 with 2D-TEE and 21 with 3D-TEE and complex repair was done in 18 with 2D-TEE and 26 with 3D-TEE. Importantly, three patients with 2D-TEE before surgery had to undergo reoperation due to recurrent severe mitral regurgitation with dehiscence of the annuloplasty rings, although none with 3D-TEE did. Conclusions These results demonstrate that 3D-TEE is helpful in assessing the morphology of mitral apparatus and complexity of mitral valve repair, particularly in minimally invasive cardiac surgery including robotic ones. We would suggest that sonographers, cardiologists, and cardiac surgeons should be familiar with 3D-TEE and work together throughout the perioperative period for better outcomes.